2006
DOI: 10.1172/jci27209
|View full text |Cite
|
Sign up to set email alerts
|

Expression of COX-2 in platelet-monocyte interactions occurs via combinatorial regulation involving adhesion and cytokine signaling

D. A. Dixon

Abstract: Tight regulation of COX-2 expression is a key feature controlling eicosanoid production in atherosclerosis and other inflammatory syndromes. Adhesive interactions between platelets and monocytes occur in these conditions and deliver specific signals that trigger inflammatory gene expression. Using a cellular model of monocyte signaling induced by activated human platelets, we identified the central posttranscriptional mechanisms that regulate timing and magnitude of COX-2 expression. Tethering of monocytes to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
101
0
9

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(116 citation statements)
references
References 68 publications
(172 reference statements)
6
101
0
9
Order By: Relevance
“…A possible mechanism to explain the discrepancy between mRNA accumulation and protein synthesis of COX-2 is that platelets switched on a stabilization pathway of COX-2 mRNA (Dixon et al, 2006). This hypothesis was addressed by comparing COX-2 mRNA levels in HT29 cells cocultured with platelets for 20 hours versus 4 hours or in HT29 cells cultured alone in the presence of actinomycin D to stop transcription.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A possible mechanism to explain the discrepancy between mRNA accumulation and protein synthesis of COX-2 is that platelets switched on a stabilization pathway of COX-2 mRNA (Dixon et al, 2006). This hypothesis was addressed by comparing COX-2 mRNA levels in HT29 cells cocultured with platelets for 20 hours versus 4 hours or in HT29 cells cultured alone in the presence of actinomycin D to stop transcription.…”
Section: Resultsmentioning
confidence: 99%
“…HT29 cells (0.5 Â10 6 cells) were cultured alone or with platelets (0.5 Â 10 8 ) for 2, 4, and 20 hours; then culture media were collected and cells were washed twice with PBS and fixed in cold acetone/methanol solution (40:60) for 20 minutes at room temperature. COX-2, COX-1, HuR, and GAPDH immunostaining were detected as previously reported (Dixon et al, 2006), and a detailed description is reported in Supplemental Methods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a recent report using a preparation of platelets and monocytes has shown that efficient induction of COX-2 protein requires combination of signals involving activation of jB-driven transcriptional activation and stabilization of COX-2 mRNA by silencing the AU-rich mRNA element [51]. Whereas cells with a lasting life span might need combination of mechanisms for a timely regulation of COX-2 protein expression, the existence of rapid regulatory mechanisms in short-lived cells such as PMN seems most appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Such circumstances can trigger the conformational changes of integrins and further augment the adhesive capacity of leukocytes (da Costa Martins et al, 2006;Piccardoni et al, 2001). The binding of P-selectin to PSGL-1 could also induce a series of inflammatory responses, including nuclear translocation of NF-B and the gene expression of various inflammatory cytokines, which is essential for the inflammatory phenotype acquisition of leukocytes (Dixon et al, 2006;Weyrich et al, 1996). The processes of platelet interaction with ECs and leukocytes are complicated and involve a great deal of conformational and functional alterations, which may contribute to the augmented leukocyte adhesion to ECs.…”
Section: Figurementioning
confidence: 99%